Perlindungan Hukum Bagi Pemilik Hak Merek yang Sudah Terdaftar - A, Ardiansyah; Atmoko, Dwi; Lestari, Melanie Pita (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
A brand is an image for a manufacturer and a good name for a company, but it is also part of a business strategy. There is no manufacturer that does not use a trademark as an identity for the products it produces or the services it provides. The identity of a brand is a distinguishing characteristic and differentiates a company's brand from other company brands. Therefore, brand disputes often arise. The research method used is normative juridical. As a result of this research, it was found that trademark registration can end due to the expiry of the validity period of the trademark, deletion of a trademark due to the trademark owner's own request, deletion of a registered trademark at the initiative of the Minister after receiving a recommendation from the Mark Appeal Commission, and deletion of a trademark due to a lawsuit from a party third. Trademark protection exists from the moment of trademark registration and trademark protection is valid for 10 years during the period of trademark registration and can be extended for the same period. Lawsuits are filed for either civil lawsuits, criminal charges or lawsuits. Administrative action in the form of rejection and cancellation of trademark registration.